2021
DOI: 10.1007/s40843-021-1832-2
|View full text |Cite
|
Sign up to set email alerts
|

Substitutional oxygen activated photoluminescence enhancement in monolayer transition metal dichalcogenides

Abstract: Atomically thin transition metal dichalcogenides (TMDCs) are intriguing semiconductors for photonics and optoelectronics, and therefore enhancing their photoluminescence (PL) efficiency is crucial for these applications. Many efforts have been contributed to enhancing the PL performance of monolayer TMDCs, yet the complexity between the microstructure and the PL efficiency has hindered the manipulation of their PL properties. Here we demonstrate that the PL intensity of the monolayer TMDC can be enhanced by ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 36 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…The significantly lower proportion of defect excitation of r-WS 2 than t-WS 2 indicates lower defect density and higher intrinsic emission of materials. [20,30,31] It is inferred that the higher defect density at the edge of t-WS 2 induces bound excitation emissions [19,20,32] and also absorbs oxygen in air, [33] contributing to the higher fluorescence intensity at the edge in Figure 2a. This spatial heterogeneity, which comes from the unstable chalcogen feeding during the CVD process, would affect charge transport in electronics [21,[34][35][36] and reduce local PL quantum yields in optoelectronics.…”
Section: Methodsmentioning
confidence: 99%
“…The significantly lower proportion of defect excitation of r-WS 2 than t-WS 2 indicates lower defect density and higher intrinsic emission of materials. [20,30,31] It is inferred that the higher defect density at the edge of t-WS 2 induces bound excitation emissions [19,20,32] and also absorbs oxygen in air, [33] contributing to the higher fluorescence intensity at the edge in Figure 2a. This spatial heterogeneity, which comes from the unstable chalcogen feeding during the CVD process, would affect charge transport in electronics [21,[34][35][36] and reduce local PL quantum yields in optoelectronics.…”
Section: Methodsmentioning
confidence: 99%
“…The significantly lower proportion of defect excitation of r-WS 2 than t-WS 2 indicates lower defect density and higher intrinsic emission of materials. [20,30,31] It is inferred that the higher defect density at the edge of t-WS 2 induces bound excitation emissions [19,20,32] and also absorbs oxygen in air, [33] contributing to the higher fluorescence intensity at the edge in Figure 2a. This spatial heterogeneity, which comes from the unstable chalcogen feeding during the CVD process, would affect charge transport in electronics [21,[34][35][36] and reduce local PL quantum yields in optoelectronics.…”
Section: Methodsmentioning
confidence: 99%
“…Luminescence of TMDCs with excitons (X 0 ), trions (X − /X + ) and biexcitons (XX) can be regulated by laser repairing or passivating of the existent defects, making the TMDCs promising defect related ODS candidates. [36,[50][51][52][53] For example, Zhao et al demonstrated that PL enhancement could be easily achieved in exfoliated monolayer WS 2 under low-power laser irradiation, because oxygen attachment played a significant role in curing sulfur vacancy (V S ). [51] Moreover, Sivaram et al demonstrated that H 2 O molecules can overcome a large adsorption barrier with the assistance of photogenerated excitons to passivate V S in the chemical vapor deposition grown MoS 2 , resulting in a 200-fold increase in PL intensity.…”
Section: Defect-related Regulationmentioning
confidence: 99%
“…[36,[50][51][52][53] For example, Zhao et al demonstrated that PL enhancement could be easily achieved in exfoliated monolayer WS 2 under low-power laser irradiation, because oxygen attachment played a significant role in curing sulfur vacancy (V S ). [51] Moreover, Sivaram et al demonstrated that H 2 O molecules can overcome a large adsorption barrier with the assistance of photogenerated excitons to passivate V S in the chemical vapor deposition grown MoS 2 , resulting in a 200-fold increase in PL intensity. [53] The photoluminescence of Ln 2+ -doped glass.…”
Section: Defect-related Regulationmentioning
confidence: 99%